Evidence for older carbon loss with lowered water tables and changing plant functional groups in peatlands. Issue 3 (10th November 2022) - Stuart, Julia E. M.; Tucker, Colin L.; Lilleskov, Erik A.; Kolka, Randall K.; Chimner, Rodney A.; Heckman, Katherine A.; Kane, Evan S.
Abstract: A small imbalance in plant productivity and decomposition accounts for the carbon (C) accumulation capacity of peatlands. As climate changes, the continuity of peatland net C storage relies on rising primary production to offset increasing ecosystem respiration (ER) along with the persistence of older C in waterlogged peat. A lowering in the water table position in peatlands often increases decomposition rates, but concurrent plant community shifts can interactively alter ER and plant productivity responses. The combined effects of water table variation and plant communities on older peat C loss are unknown. We used a full‐factorial 1‐m 3 mesocosm array with vascular plant functional group manipulations (Unmanipulated Control, Sedge only, and Ericaceous only) and water table depth (natural and lowered) treatments to test the effects of plants and water depth on CO2 fluxes, decomposition, and older C loss. We used Δ 14 C and δ 13 C of ecosystem CO2 respiration, bulk peat, plants, and porewater dissolved inorganic C to construct mixing models partitioning ER among potential sources. We found that the lowered water table treatments were respiring C fixed before the bomb spike (1955) from deep waterlogged peat. Lowered water table Sedge treatments had the oldest dissolved inorganic 14 C signature and the highest proportional peat contribution to ER. Decomposition assays corroborated sustained high rates of decomposition with lowered water tables down to 40 cm below the peat surface. Heterotrophic respiration exceeded plant respiration at the height of the growing season in lowered water table treatments. Rates of gross primary production were only impacted by vegetation, whereas ER was affected by vegetation and water table depth treatments. The decoupling of respiration and primary production with lowered water tables combined with older C losses suggests that climate and land‐use‐induced changes in peatland hydrology can increase the vulnerability of peatland C stores. Abstract : The combined effects of water table variation and plant community changes on the loss of older carbon in peatlands is currently unknown. We found that lowered water tables induced the loss of older (before 1950) carbon in both sedge and ericaceous plant dominated plots, with the oldest carbon lost in sedge dominated plots. We also saw higher decomposition rates below 10 cm in the peat and a decoupling of gross primary productivity and ecosystem respiration rates with lowered water tables.